1987
DOI: 10.1093/rheumatology/26.6.416
|View full text |Cite
|
Sign up to set email alerts
|

Back Pain and Sciatica: Controlled Trials of Manipulation, Traction, Sclerosant and Epidural Injections

Abstract: Four treatment regimens for patients with specified combinations of low back pain and sciatica were evaluated. The largest group studied had low back pain with limited straight-leg raising (SLR) and in them the beneficial effect of manipulation in hastening pain relief was highly significant. In similar patients without limitation of SLR, the effect was of borderline significance. In all the other groups, treated patients also recovered more quickly than their controls. Traction, for patients with low back pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(131 citation statements)
references
References 0 publications
4
120
0
7
Order By: Relevance
“…This finding agrees to the current literature review result [28,38]. The randomized control trial with relatively acceptable method score [38], included subjects with neurological deficit involvement did not support to use mechanical lumbar traction for LBP management.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding agrees to the current literature review result [28,38]. The randomized control trial with relatively acceptable method score [38], included subjects with neurological deficit involvement did not support to use mechanical lumbar traction for LBP management.…”
Section: Discussionsupporting
confidence: 89%
“…There is no randomized control trial has acceptable method score with exclusive criteria of subjects having neurological deficit. Only one study with minimal method score supported the use of mechanical lumbar traction for management of LBP patients without neurological deficits [28]. Yet, majority of literatures published in peer review journals did not specify the detail of the neurological deficit and radicular leg pain in their inclusive criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this review are shown in Table 2. Four of the six included trials [12,14,33,50] are in fact a comparison of ESIs with a control. The study by Dashfield [25] compared steroid epidurals to targeted steroid placement during spinal endoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The Cochrane review included six pragmatic trials that reported on short-term pain relief [8,22,38,63,77,78]. Four of these six trials showed a non-significant positive effect of corticosteroids compared to other procedures.…”
Section: Epidural Injections Vs Other Interventionsmentioning
confidence: 99%